2012
DOI: 10.1021/ef300569n
|View full text |Cite
|
Sign up to set email alerts
|

Bed Agglomeration Characteristics in Fluidized-Bed Combustion of Biomass Fuels Using Olivine as Bed Material

Abstract: The bed agglomeration characteristics during combustion of typical biomass fuels were determined in a bench-scale bubbling fluidized-bed reactor (5 kW) using olivine and quartz sand as bed material. The fuels studied include willow, logging residues, wheat straw, and wheat distiller’s dried grain with solubles (wheat DDGS). Bed material samples and agglomerates were analyzed by means of scanning electron microscopy coupled with energy-dispersive X-ray spectroscopy (SEM–EDS), for morphology and elemental compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
85
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(96 citation statements)
references
References 26 publications
9
85
2
Order By: Relevance
“…Advanced thermodynamic equilibrium modelling has become a widely used method [15,17,26,45,46,48,53] it is an important tool for studying high temperature processes and ash-forming elements in biomass and waste combustion and gasification [26,41,[49][50][51]. The method is fast and cost effective.…”
Section: Thermodynamic Equilibrium Modellingmentioning
confidence: 99%
“…Advanced thermodynamic equilibrium modelling has become a widely used method [15,17,26,45,46,48,53] it is an important tool for studying high temperature processes and ash-forming elements in biomass and waste combustion and gasification [26,41,[49][50][51]. The method is fast and cost effective.…”
Section: Thermodynamic Equilibrium Modellingmentioning
confidence: 99%
“…Previous studies showed an interaction between bed particles and ash during combustion of biomass feedstock. As a consequence of this interference calcium-rich layers are built around bed particles [8][9][10]. Investigations of time dependence regarding layer formation on quartz sand particles from a 30 MW th bubbling fluidized bed biomass combustion plant showed several steps of layer growth.…”
Section: Introductionmentioning
confidence: 99%
“…During the initial phase of layer formation, the growth rate was relatively high, but decreased over time [11]. A correlation between bed particle layer formation and bed agglomeration has been established, mainly focusing on combustion of wood fuels [8,9,[12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Grimm et al 26 studied the fluidized bed combustion of different biomass fuels and compared the agglomeration tendencies with olivine and quartz as bed materials. Using woody biomass, significant difference in agglomeration 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 temperature between quartz and olivine was reported.…”
Section: Introductionmentioning
confidence: 99%